Pengaruh kualitas pelayanan, bauran pemasaran, terhadap kepuasan nasabah bank era covid-19 - Rumiyati Rumiyati; Afriapollo Syafarudin (Forum Kerjasama Pendidikan Tinggi, 2021)
Building loyalty is no longer an option in the banking world. In recent years a trend has emerged, namely the tendency for customers to have more than one savings account at different banks. One of the ways to do this is by marketing service quality and marketing mix to customer satisfaction. The Bank's compliance with government policies to prevent the spread of COVID-19 is the Work From Home policy. Banking measures to optimize employee efforts to maintain the health of their closest people at home while providing maximum protection from the potential for contracting COVID-19 while interacting with the community while working or traveling to and from the office, namely adjustments to work systems. The role of marketing in banking is to build strong relationships in a sustainable manner by providing excellent service for the development of service quality such as Servqua, with Tangible, Responsiveness, Reliability, Assurance, and Emphaty characteristics. New service quality that can be applied in the banking world in particular. The most important thing is Banking Service Quality (BSQ.) Like conventional bank service products, the bank's low rating. Testing using the PLS (Partial Least Square) analysis method. The results showed that customer satisfaction has a positive and significant effect on customer loyalty. Customer satisfaction affects the reliability, effectiveness and assurance of the service portfolio, price and access. Tangible must receive extra attention so that customer satisfaction can increase